2021
DOI: 10.1002/jeab.706
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral economics and safe sex: Examining condom use decisions from a reinforcer pathology framework

Abstract: Condom use substantially reduces unwanted pregnancies and sexually transmitted infections. While condom availability is a significant public health priority, effects of condom availability constraints remain relatively under‐researched. The limited research on condom availability suggests two major barriers to use: (1) effort/costs and (2) delay to access. To date, we are aware of no study that explores both demand for and discounting of condom availability; the focus of this study was to account for condom de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…Foreign scholars' research on media and sex education and sexuality dates back as far as the 1980s and 1990s, and may be related to the earlier spread of sex education abroad, which is important for our country to absorb the essence from both the spread of sex education and research. Harsin, Gelino and Strickland's (2021) study not only notes the following major barriers, such as energy consumption, delayed access, and financial burden, but also verified that low discounted contraceptives is significantly correlated with higher willingness to engage in unprotected sex, which has essential implications for the hypothesis regarding perceived behavioral control proposed in this study [5]. In addition, two theories mentioned in Brown's (2002) study that are also instructive for this study are Cultivation Theory and Social Learning Theory [6].…”
Section: Foreign Research Resultssupporting
confidence: 64%
“…Foreign scholars' research on media and sex education and sexuality dates back as far as the 1980s and 1990s, and may be related to the earlier spread of sex education abroad, which is important for our country to absorb the essence from both the spread of sex education and research. Harsin, Gelino and Strickland's (2021) study not only notes the following major barriers, such as energy consumption, delayed access, and financial burden, but also verified that low discounted contraceptives is significantly correlated with higher willingness to engage in unprotected sex, which has essential implications for the hypothesis regarding perceived behavioral control proposed in this study [5]. In addition, two theories mentioned in Brown's (2002) study that are also instructive for this study are Cultivation Theory and Social Learning Theory [6].…”
Section: Foreign Research Resultssupporting
confidence: 64%
“…Other research has shown how cost can impact decisions to engage in protected sexual activities (e.g., use of condoms in casual sexual encounters). A synthesis of findings (see Dolan et al, 2020; Harsin et al, 2021; Strickland et al, 2020) underscores the importance of low-cost, easily accessed condoms to maximize the likelihood of timely and appropriate use. These findings show how ongoing CPT applications can show how substantive public health benefits can be reached by a keener understanding of seemingly small environmental changes (e.g., reducing the burden on obtaining condoms in commercial spaces).…”
Section: Unique Insights From the Cptmentioning
confidence: 99%
“…Demand is often analyzed in a demand curve, which displays the functional relation between the amount of a commodity/activity consumed and its price. Demand analysis has been used to quantify the likelihood of initiating and continuing other health‐related behaviors, such as treatment selection (Gilroy & Feck, 2022; Gilroy et al, 2022), drug use (e.g., Jacobs & Bickel, 1999; MacKillop et al, 2008; Murphy & MacKillop, 2006), food intake (e.g., Epstein et al, 2010, 2018), problematic technology use (e.g., Hayashi & Blessington, 2021; Hayashi et al, 2019a, 2019b), risky sex (e.g., Dolan et al, 2020; Harsin et al, 2021; Jarmolowicz et al, 2016; Strickland et al, 2020), medication adherence (e.g., Jarmolowicz et al, 2019, 2020), and exercising (e.g., Anokye et al, 2012). In a typical demand task, consumption is quantified by the amount of a commodity/activity consumed at a given price, but it can also be quantified by the probability of a commodity/activity consumed (Roma et al, 2016, 2017).…”
Section: Breastfeeding and Behavioral Economic Demand Analysismentioning
confidence: 99%